Si kecil cerdas obat: Edukasi penggunaan obat yang aman untuk anak SD - Arshy Prodyanatasari; Dyah Ayu Kusumaratni; Adi Laksono; Mely Purnadianti; Mardiana Putri Prasetyani; Krisnita Dwi Jayanti (Abdimas Altruis: Jurnal Pengabdian kepada Masyarakat, 2026)
The community service activity was carried out in response to the high number of cases of medication misuse among children, with initial surveys showing that 65% of 4th-5th grade elementary school students in Kediri had taken medication without adult supervision, and 80% did not understand basic dosage rules. The programme, involving 44 students from SDN Bujel 3 Elementary School in Kediri City, was designed to improve health literacy through the Participatory Action Research (PAR) method, comprising three main stages: (1) initial assessment via a pre-test, (2) intervention in the form of interactive education and demonstrations on how to read medication labels, and (3) evaluation using a post-test and observation of skills. Based on the pre-test and post-test analyses, there was a 45% increase in participants' understanding, with only 40% of students correctly answering questions about medication dosages in the pre-test, increasing to 85% in the post-test. Based on these findings, it was concluded that the PAR approach effectively improved students' understanding and skills. For sustainability, the following recommendations were made: (1) developing digital modules, (2) involving parents in follow-up programmes, and (3) strengthening teachers' capacity through training as school health facilitators to ensure programme sustainability. This activity demonstrates that participatory health education can create sustainable behavioural change in school-age children.